Connectors and Dividers : The Challenges and Prospects for Conflict Transformation in Kashmir and Sri Lanka - Singh, Shweta (Brill | Manohar Publishers & Distributors, 2015)
South Asia is characterised by a change in the nature of contemporary armed conflict, a shift from interstate to intrastate armed conflict. This change is closely enmeshed in post-colonial concerns of competing national identities, historical memories, politics of deprivation and legitimacy. It creates challenges for scholars, policymakers and practitioners alike, who are to develop responses to conflicts in South Asia. The liberal, state-centric emphasis in the fields of political science and international relations often precludes a civil society-initiated contextual analysis that focuses on societal tensions. Therefore, there is a significant lacuna in the literature that can inform policy on a practical level. This monograph aims to compensate for this lacuna by providing a comparative analysis of societal Connectors and Dividers (C&D) in Kashmir and Sri Lanka that have the potential to inform policy. This empirical work utilises the C&D analytical tool within the Do No Harm Framework (Anderson 1999), in order to uncover the hidden potential within the tool to aid policy implementation at a national level, and to provide pathways for Conflict Transformation in Kashmir and Sri Lanka. The C&D tool is widely utilised in evaluating humanitarian projects, to assess whether any of the actions may result in an unintended negative repercussion, while progressing with the project outcomes. However, at a national policy-setting level, this tool is unused. It is argued that sustainable conflict transformation hinges on imaginative capacities to transcend vicious cycles of violence. Published as Volume 61 in the series RCSS Policy Studies .